Diseño de una guía para la erradicación del maltrato juvenil “Bullying” y su incidencia en los procesos educativos en el colegio “Trajano Naranjo Iturralde” de la cuidad de Latacunga parroquia Juan Montalvo en el año lectivo” 2012-2013 - Cóndor Lara, Lina María (2016)
The scholar harassment also known by its English term bullying (frightened) is any form of physical, psychological, verbal abuse or produced between schools repeatedly along a determinate time the victim is subjected to a kind of methodical and systematic torture for the aggressor and the other schoolmates can assume the position of indifference, silence and complicity. From this perspective violence or abuse is a physical persecution and / or psychological behavior that makes the pupil against another, that chooses a victim of repeated attacks; this negative and hostile action, puts victims in positions that can hardly get out by their means, moreover violence is never justified and excused, all are victims and responsible because people do not mind this problem and sometimes the results are disastrous; for this reason this research aims to eradicate youth abuse "Bullying" and its impact on educational processes in students of the Colegio “Technical Trajano Naranjo Iturralde , through designing and implementing a guide that will allow authorities, teachers and Students take necessary corrective to this educational problem, which will make students live in a tranquility atmosphere within the educational institution and it is great importance because it becomes an effective tool for the development of good educational live.